The Effectiveness of Physical Therapy Technology for Female Cheerleaders with Impaired Spatial Body Organization - Grygus, Igor; Zeiser, Tetyana (Journal of Education, Health and Sport, 2026)
Despite a profound understanding of biomechanical changes in the spatial organization of athletes’ bodies, the further study and implementation of effective physical therapy technologies for preventing functional disorders of the musculoskeletal system remains a highly relevant task for rehabilitation specialists. The aim of the study is to evaluate the effectiveness of physical therapy technology for correcting spatial body organization disorders in female cheerleaders at the initial stage of training. Material and Methods The study involved 20 girls aged 7–8 years identified with slouched or scoliotic posture types. Research methods included: theoretical analysis of specialized literature; medico-biological methods (photography), visual posture screening, and methods of mathematical statistics. Results Following an individualized physical therapy course focused on restoring sagittal balance, shoulder girdle symmetry, and trunk stabilization, a decrease in the proportion of girls with low posture levels and a corresponding increase in the medium level was observed. Specifically, among seven-year-old athletes with slouched posture, the number of girls at the low level was halved (from 50% to 25%). Similar trends were noted among athletes of the same age with scoliotic posture, where only 20% remained at the low level. The shifts in the 8-year-old group were particularly significant. In cheerleaders with slouched posture, the low-level percentage decreased to 16.7%, while 83.3% reached the medium level. A similar pattern was observed in cheerleaders with scoliotic posture, where no more than 20% remained at the low level of the biogeometric posture profile. Conclusions Experimental testing of the author’s technology demonstrated its effectiveness in improving the spatial body organization of young female cheerleaders aged 7–8 with slouched and scoliotic posture types. A clear positive dynamics was established across key indicators of the biogeometric profile.